Computational fluid dynamics simulation of rotor cooling system in interior permanent magnet motor / Muhammad Amirul Asri Ahmad Lukman - Muhammad Amirul Asri, Ahmad Lukman (2021)
This study presents a interior permanent magnet (IPM) motor using rotor cooling to enhance the cooling system of the motor. The IPM motor applies the forced cooling method where channels were provided in the entire motor from its’ housing to the rotor through the designated paths in the cooling system. This designated paths consists of upper housing, housing jacket, lower housing, and hollow shaft. With the cooling system circulation inside the IPM motor, an effective cooling can be achieved as compared to the conventional approach of cooling. A modified coolant path is designed for optimization with different coolant used between water and oil. Once the cooling boundary was selected, the numerical model of the Motor Housing Cooling System of the IPM will be modelled and simulated. Temperatures at different locations of different coolant path design and coolant medium of water and oil were modelled and the numerical results is presented. After iterations, Case 1 suggests oil as a better cooling medium. However, in Case 2, the manipulation of motor housing of the coolant path itself influence the cooling effect and suggests the same cooling effect can be achieved at midpoint of the housing coolant path. Although the outlet of Case 2 suggests a lesser cooling effect, this finding where the improved housing coolant path opens the possibility of further study towards a better understanding of the characteristics of the cooling effect and finally optimize by saving on oil consumption whilst optimizing the pattern of the coolant path.